1986
DOI: 10.1017/s0043174500068119
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Translocation, and Toxicity of Glyphosate and Oxyfluorfen in Yellow Nutsedge (Cyperus esculentus)

Abstract: The potential for yellow nutsedge (Cyperus esculentusL. var.leptostachyusBoeck. # CYPES) regrowth was reduced by increasing plant age and by glyphosate [N-(phosphonomethyl)glycine] and oxyfluorfen [2-chloro-1-(3-ethoxy-4-nitrophenoxy)-4-(trifluoromethyl)benzene]. Of the amount of glyphosate transported to underground parts, most was found in the tubers, with immature rhizomes, roots, and tubers having 2 to 3 times higher concentrations than comparable mature tissues. Addition of unlabeled oxyfluorfen as a tank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
2
18
1
1
Order By: Relevance
“…The additive effect provided by the glyphosate + carfentrazone-ethyl mixture has been reported by previous authors, and the compatibility between them depends on the doses of the herbicides used in the mixture and on the species of weed under assessment (Werlang & Silva, 2002). The increase in glyphosate efficacy by its association with herbicides sharing the mechanism of action of carfentrazone-ethyl has been observed in previous studies (Pereira & Crabtree, 1986;Wells & Appleby, 1992). The mixture of low doses of lactofen with glyphosate increased the accumulation of shikimate in the tissues of plants of Malva parviflora (Wells & Appleby, 1992).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The additive effect provided by the glyphosate + carfentrazone-ethyl mixture has been reported by previous authors, and the compatibility between them depends on the doses of the herbicides used in the mixture and on the species of weed under assessment (Werlang & Silva, 2002). The increase in glyphosate efficacy by its association with herbicides sharing the mechanism of action of carfentrazone-ethyl has been observed in previous studies (Pereira & Crabtree, 1986;Wells & Appleby, 1992). The mixture of low doses of lactofen with glyphosate increased the accumulation of shikimate in the tissues of plants of Malva parviflora (Wells & Appleby, 1992).…”
Section: Resultssupporting
confidence: 60%
“…Control of Macroptilium atropurpureum at 28 days after herbicide application These authors believe that lactofen promotes the entry of glyphosate into the cells. Pereira & Crabtree (1986) reported an improvement in the absorption and translocation of glyphosate in plants of Cyperus esculentus after the addition of oxyfluorfen. The increase in the accumulation of shikimate and in the absorption, cell penetration, and translocation of glyphosate as a result of adding herbicides that inhibit PPO may explain the increased efficacy of the mixture glyphosate + carfentrazoneethyl under full sunlight conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Yellow nutsedge is difficult to control with glyphosate. The glyphosate application rate and the plant age at the time of application influence yellow nutsedge control and viable tuber production (Appleby and Paller 1978;Keeley et al 1985;Pereira and Crabtree 1986;Stoller et al 1975). Regrowth of yellow nutsedge after an application of glyphosate at 1.1 to 2.2 kg/ha (Pereira and Crabtree 1986) and, conversely, control with glyphosate at 1.1 kg/ha or more (Derr and Wilcut 1993;Stoller et al 1975) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…(Salisbury et al 1991), quackgrass [Elytrigia repens (L.) Nevski] (Claus and Behrens 1976), hemp dogbane (Apocynum cannabinum L.) (Schultz and Burnside 1980), Canada thistle [Cirsium arvense (L.) Scop.] (Darwent et al 1994), purple nutsedge (Cyperus rotundus L.) (Bariuan et al 1999;Zandstra et al 1974), and yellow nutsedge (Appleby and Paller 1978;Pereira and Crabtree 1986;Stoller et al 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of carbon fixation in bright light causes rapid photo-oxidative damage due to uncontrolled dissipation of absorbed light energy, ultimately resulting in cell disruption. Herbicides that cause cell disruption often reduce the absorption and/or the translocation of other herbicides applied in mixture (Croon et al 1989;Culpepper et al 1999;Olson and Nalewaja 1982;Pereira and Crabtree 1986). The objective of this study was to characterize absorption and translocation of glyphosate applied alone and in mixture with MSMA to determine if reduced absorption or translocation is the cause of antagonism of glyphosate with MSMA in browntop millet and Palmer amaranth.…”
mentioning
confidence: 99%